Framing Agama Dalam Politik Praktis (Studi tentang Wacana Politik Keagamaan Partai Keadilan Sejahtera) - Yuniartin, Titin (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2019)
This paper discusses the political identity of the Prosperous Justice Party (PKS). PKS is one of the parties based on Islam but stands firmly in the auspices of the Unitary State of the Republic of Indonesia. PKS is born from movement, LDK-KAMMI-PK-PKS. The ideals of the Khilafah Islamiyah are always present in the ideals of the movement. Although in the auspices of plural and multicultural country, the PKS still exists to adjust with the Republic of Indonesia. PKS political identity for some may seem gray. This is understandable, especially if we look at it from the perspective of incomplete Islamic understanding. The concept of the caliphate of Islamiyah ala PKS is different from what is understood and developed in other activism. In essence, the Islamic caliphate that the PKS wants to uphold is international justice, international welfare, international harmony, and world prosperity. It starts from building prosperity, harmony, and national justice.